Surgical Treatment of Classic Kaposi’s Sarcoma in the Lower Extremity - Adem Topkara; Adem Özkan; Ramazan Hakan Özcan; Mustafa Öksüz; Neşe Çallı Demirkan (Turkish Journal of Plastic Surgery, 2017)
Objective: Classic Kaposi’s sarcoma is an indolent, angioproliferative tumor that is usually observed in the lower extremities of elderly men. Depending on their stages, skin lesions are maculonodular or vegetative ulcerated masses. Visceral organ or lymph node involvement may rarely occur. There is no gold standard treatment for local diseases. Surgical excision, radiotherapy, chemotherapy, and cryotherapy can be performed. This retrospective study aimed to evaluate the long-term results of surgical excision and skin graft repair of stage I and II classic Kaposi’s sarcoma skin lesions around the foot and ankle. Material and Methods: Eleven patients were included. The patients’ age and gender, location of lesion, surgical treatment, follow-up period, and recurrence were evaluated by retrospectively examining patient records. For the surgical treatment, the lesion was excised with a 0.5-cm safe skin margin. The defect area was repaired with full-thickness skin grafts that were obtained from the inguinal region in all patients. Results: Eight of the patients were male and three were female. The average age of the patients was 69 (54–84) years. All patients were completely cured. The average follow-up period was 1.8 (1–3) years. No recurrence was observed in any of the patients at the end of the follow-up period. Conclusion: Classic Kaposi’s sarcoma skin lesions in the lower extremity can be completely cured by surgical excision, with no recurrence risk. After surgical excision, using a full-thickness skin graft for repairing primary cutaneous defects, particularly those in the soles, is a simple and reliable method.